Combustion performance and sodium transformation of high-sodium ZhunDong coal during chemical looping combustion with hematite as oxygen carrier. (1st November 2015) - Ge, Huijun; Shen, Laihong; Gu, Haiming; Song, Tao; Jiang, Shouxi
Highlights: CLC with hematite OC is an appropriate technology for processing ZhunDong coal. Combustion performance of high-sodium ZhunDong coal is better than that of other types of coal in CLC. CLC of high-sodium ZhunDong coal is conducive to the control of nitrogen contamination release. High melting point sodium aluminosilicate, Na2 O · Al2 O3 · 6SiO2, formed in CLC fly ash. Abstract: Chemical looping combustion (CLC) of ZhunDong coal (ZD) with hematite as oxygen carrier (OC) is an appropriate solution of how to utilize abundant ZD without severe slagging and fouling problems. At first, the combustion performance of ZD was compared to that of other three types of Chinese coals. Due to the catalytic effect of sodium in ZD, carbon capture efficiency, carbon conversion efficiency, CO2 concentration of fuel reactor and CO2 capture efficiency were all evidently higher than the ones for other types of coals at the same temperature. In addition, no NO2 was detected, and N2 O and NO were the sole nitrogen contaminations in CLC of ZD. The high volatile content together with carbon gasification rate for ZD was conducive to the control of nitrogen contamination release. At last, 10 h of continuous operation with ZD has been accomplished to evaluate the characteristic of hematite OC and sodium formation in hematite or fly ash. Hematite showed high reactivity in the continuous operation and the porous properties of 5 h-hematite was best. High sodium content is the most prominent feature of ZD. Although there are also a large amount of other phases in ZD, due to the better catalytic effect, sodium is inferred to be the main factor accelerating the carbon conversion and improving the porous properties of OC. Moreover, it was found that there was a high melting point sodium aluminosilicate, Na2 O · Al2 O3 · 6SiO2 instead of low melting point sodium silicates formed in the CLC fly ash, mitigating the severe slagging and fouling problems.